Adaptasi Masyarakat Pekalongan Terhadap Sampah: Antara Kesadaran Dan Ketidaksiapan - Pasya, Mohammad Rafa’at; Adinugraha, Hendri Hermawan; Gunawan, Ade (LPPM IAIN Sorong, 2025)
This study explores the adaptive behavior of the people of Pekalongan in addressing the increasing waste problem within their urban environment. The research aims to investigate the level of public awareness and readiness to manage waste sustainably. Using a qualitative descriptive approach, the study employed observations, interviews, and document analysis as data collection techniques. Results reveal a significant gap between awareness and action. While many residents understand the environmental and health impacts of unmanaged waste and express support for waste management initiatives, actual practices such as littering and burning waste remain prevalent. Infrastructure inadequacies and lack of consistent government enforcement contribute to this gap. Community organizations and environmental NGOs have initiated efforts like waste banks and door-to-door education, yet their reach remains limited. The study concludes that an integrated, collaborative approach involving the government, civil society, and local communities is essential to build a sustainable and participatory waste management system rooted in local values. This research contributes to the development of strategies that empower communities as active agents of environmental change.